Improvement of Electrical Conductivity in Conjugated Polymers through Cascade Doping with Small-Molecular Dopants - Yoon, Sang Eun; Park, Jaehong; Kwon, Ji Eon; Lee, Sang Yeon; Han, Ji Min; Go, Chae Young; Choi, Siku; Kim, Ki Chul; Seo, Hyungtak; Kim, Jong H.; Kim, Bong Gi (Advanced Materials, 2020)
Doping capability is primitively governed by the energy level offset between the highest occupied molecular orbital (HOMO) of conjugated polymers (CPs) and the lowest unoccupied molecular orbital (LUMO) of dopants. A poor doping efficiency is obtained when doping directly using NOBF4 forming a large energy offset with the CP, while the devised doping strategy is found to significantly improve the doping efficiency (electrical conductivity) by sequentially treating the NOBF4 to the pre-doped CP with 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquino-dimethane (F4TCNQ), establishing a relatively small energy level offset. It is verified that the cascade doping strategy requires receptive sites for each dopant to further improve the doping efficiency, and provides fast reaction kinetics energetically. An outstanding electrical conductivity (>610 S cm−1) is achieved through the optimization of the devised doping strategy, and spectroscopy analysis, including Hall effect measurement, supports more efficient charge carrier generation via the devised cascade doping.
Keywords: Charge carrier generation; Doping efficiency; Doping strategies; Electrical conductivity; Fast reaction kinetics; Hall effect measurement; Highest occupied molecular orbital; Lowest unoccupied molecular orbital; doping; doping efficiency; doping mechanisms; molecular dopants; organic conductors